MiR‐34a is upregulated in AIP‐mutated somatotropinomas and promotes octreotide resistance. Issue 12 (10th September 2020) - Bogner, Eva‐Maria; Daly, Adrian F.; Gulde, Sebastian; Karhu, Auli; Irmler, Martin; Beckers, Johannes; Mohr, Hermine; Beckers, Albert; Pellegata, Natalia S.
Abstract: Pituitary adenomas (PAs) are intracranial tumors associated with significant morbidity due to hormonal dysregulation, mass effects and have a heavy treatment burden. Growth hormone (GH)‐secreting PAs (somatotropinomas) cause acromegaly‐gigantism. Genetic forms of somatotropinomas due to germline AIP mutations ( AIP mut+) have an early onset and are aggressive and resistant to treatment with somatostatin analogs (SSAs), including octreotide. The molecular underpinnings of these clinical features remain unclear. We investigated the role of miRNA dysregulation in AIP mut+ vs AIP mut− PA samples by array analysis. miR‐34a and miR‐145 were highly expressed in AIP mut+ vs AIP mut− somatotropinomas. Ectopic expression of AIP mut (p.R271W) in Aip −/− mouse embryonic fibroblasts (MEFs) upregulated miR‐34a and miR‐145, establishing a causal link between AIP mut and miRNA expression. In PA cells (GH3), miR‐34a overexpression promoted proliferation, clonogenicity, migration and suppressed apoptosis, whereas miR‐145 moderately affected proliferation and apoptosis. Moreover, high miR‐34a expression increased intracellular cAMP, a critical mitogenic factor in PAs. Crucially, high miR‐34a expression significantly blunted octreotide‐mediated GH inhibition and antiproliferative effects. miR‐34a directly targets Gnai2 encoding Gαi2, a G protein subunit inhibiting cAMP production. Accordingly, Gαi2 levels were significantly lower in AIP mut+ vs AIP mut− PA. Taken together, somatotropinomas with AIP mutations overexpress miR‐34a, which in turn downregulates Gαi2 expression, increases cAMP concentration and ultimately promotes cell growth. Upregulation of miR‐34a also impairs the hormonal and antiproliferative response of PA cells to octreotide. Thus, miR‐34a is a novel downstream target of mutant AIP that promotes a cellular phenotype mirroring the aggressive clinical features of AIP mut+ acromegaly. Abstract : What's new? Germline mutations in the AIP gene are a significant cause of inherited intracranial pituitary adenoma (PA). AIP mutation‐positive ( AIP mut+) PAs are characterized by early tumor onset, aggressive tumor behavior, and resistance to somatostatin analogs (SSAs). Here, the microRNA‐34a (miR‐34a) was found to be upregulated in AIP mut+ PA, where it correlates with pro‐oncogenic features, high cAMP levels, and impaired response to octreotide, a first‐generation SSA. In vitro, miR‐34a directly targeted GNAI2, the gene encoding Gαi2, an inhibitor of cAMP synthesis known to be downregulated in AIP mut+ adenomas. Together, miR‐34a and Gαi2 may be valuable biomarkers for therapeutic stratification of AIP mut+ patients.